A Policy Analysis of Islamic Education Budget in Indonesia - Choirul Mahfud (Edukasia Islamika : Jurnal Pendidikan Islam, 2019)
Budget policies for Islamic education in contemporary Indonesia, especially in the post-New Order era, are still within the authority of the management of the Ministry of Religion (Kemenag) of the Republic of Indonesia. In terms of quantity, the amount of budget obtained is still in the low category compared to the national education budget received by the Ministry of Education and Culture (Kemdikbud) and Kemenristekdikti. Moreover, the budget received by the Ministry of Religion is not all for the implementation of Islamic educational institutions but also for other non-Islamic educational institutions which are the responsibility of the Ministry of Religion. Therefore, this paper discusses how the policy of the Islamic education budget in Indonesia. Also, what is the impact of these policies on the implementation and sustainability of the quality of Islamic education in Indonesia